Estimation of adjustment factors for standardizing age and season corrected 305 day milk yield and estimation of heritability and repeatability of stadardized milk yield of Red Chittagong cattle - Afroz, M A; Hoque, M A; Habib, M A; Carvalheira, J G V; Bhuiyan, A K F H (The Indian Journal of Animal Sciences, 2012)
Adjustment factors for lactation milk yield to mature age and season corrected 305–day were calculated and heritability and repeatability of 305-day and test day (TD) milk yields were estimated from the nucleus herd of Red Chittagong Cattle (RCC) reared during 2005 to 2009. Lactation records (116) of 50 lactating cows were used for estimation. The factors for standardizing incomplete lactations to projected 305-day were estimated by taking 4 calving age groups (<4, 4–5, 5–6, and 6+ years of age) and 3 seasons (mid Feb to mid June, summer; mid June to mid Oct, rainy and mid October to mid Feb, winter) with the ratio factors. The heritability estimates for TD and 305-day milk yield were found as 0.41±0.08 and 0.35±0.08, respectively. Heritability estimates of individual TDs ranged from 0.24±0.33 to 0.64±0.06. Heritability of individual TD milk yield was highest in the first three months (TD2 to TD6) whereas, lowest in first few days and later after 3 months. The repeatability of 305-day and TDs milk yield were estimated as 0.28±0.12 and 0.49±0.04, respectively using intra-class correlation.